The gene for hereditary multiple exostoses does not map to the Langer-Giedion region (8q23-q24). Issue 10 (October 1992) - Le Merrer, M; Ben Othmane, K; Stanescu, V; Lyonnet, S; Van Maldergem, L; Royer, G; Munnich, A; Maroteaux, P
Abstract : Hereditary multiple exostoses is a dominantly inherited skeletal disorder which alters enchondral bone during growth and is characterised by exostoses of the juxta-epiphyseal regions. Using polymorphic DNA probes, we have been able to exclude the disease gene from close proximity to the 8q24.1 region where a dominant syndrome with multiple exostoses, the trichorhinophalangeal syndrome type II (TRP II, Langer-Giedion syndrome, MIM 15025), has been previously localised (pairwise linkage Z = -8.96 at theta = 0 with probe L48 at locus D8S51). Multipoint linkage analysis using probes L48, L24, and L1 consistently excluded the HME gene from a large area of the distal long arm of chromosome 8, spanning the smallest region of overlap assigned to the TRP II gene. These studies support the clinical view that HME and TRP II are distinct entities.